PEMIKIRAN YUSUF QARDAWI DAN ‘ABDUL ‘AZIZ BIN BAZ TENTANG BANK KONVENSIONAL (Studi Komparatif Tentang Sistem, Hukum Bekerja, dan Gaji) - Muchamad Arif Wahyudi (Maliyah : Jurnal Hukum Bisnis Islam, 2016)
Thinking between Yu>suf Qard}a>wi> and 'Abdul' Azi>z bin Baz about conventional banking system, namely Yu>suf Qard}a>wi> stating that not all transactions in conventional banking contain usury, while 'Abdul' Azi>z bin Baz stated otherwise that all transactions in conventional banks contain usury. Equation thought Yu>suf Qard}a>wi> and 'Abdul' Azi>z bin Baz compose their thoughts about the law departed from the conventional banks with the same base, namely that it is prohibited or forbidden usury. The difference is thought Yu>suf Qard}a>wi> assume that the existing systems and transactions in conventional banking is not entirely contain usury, because there are many transactions in conventional banks is lawful, good and there is no prohibition therein. As for working there for the world to be allowed because banks are not controlled by the non-Muslims, not all jobs or transactions in conventional banking classified as usury, a job as a bank clerk forced to accept because of the urgent necessities of life. While the idea of 'Abdul' Azi>z bin Baz assume the contrary that all systems, transactions and jobs that exist in conventional banks is usury, because it helps them participate in sin and transgression. As for the salary earned from working in a conventional bank according to Yu>suf Qard}a>wi> is allowed while according to 'Abdul' Azi>z bin Baz should not be or forbade.